Myself & some other being Wordsworth and the life writing - Robinson, Daniel 1969- (Muse books, 2014)
"The story of Wordsworth becoming Wordsworth by writing the fragments and drafts of what would become The Prelude, a personal poem addressed to Coleridge that he kept hidden from the public until his death in 1850. Robinson shows that, by writing about himself and that other being, Wordsworth created an innovative autobiographical epic of becoming that is the masterpiece he believed he had failed to write"..